Waste Management Based on Maqashid Shari'ah And Circular Economy: Evidence in Blitar Regency - Aryanti Nur Azizah; Ahmad Djalaluddin; Siswanto Siswanto (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2021)
The study of waste management based on maqashid shari'ah and circular economy requires a study to realize wise and Islamic waste management. This research comes with the aim to find out and analyze waste management based on maqashid shari'ah and circular economy in TPST 3R Blitar Regency, namely TPST 3R